Knowledge management-based classification method for disability-inclusive business - Ryuhei Sano (2018)
© 2014, Action for Disability Regional Rehabilitation Centre. All rights reserved. Purpose: This study provides evidence to clarify disability inclusiveness in activities of rural business. As an alternative to the analysis method that deals with disability-inclusiveness as a vague concept, knowledge management principles were applied to propose a classification method for disability-inclusive business as an emerging concept at the community level. Methods: The analysis focuses on: 1) productivity of entrepreneurs with disabilities; 2) knowledge of entrepreneurs with disabilities; and 3) understanding of customers. A total of 50 entrepreneurs with disabilities in micro and small businesses in Southeast Asia were identified in this context. Data were collected and analysed according to a story-based knowledge management approach and value chain analysis. Fuzzy logic analysis which exploited domain ontology was utilised to convert knowledge from tacit to explicit, in line with knowledge management principles. A numeric weight based on linguistic variables became available to describe each disability-inclusive business case, as well as the arrangements of fuzzy sets. Results: Out of 50 cases, 7 were classified as fully disability-inclusive while 14 were classified as not disability-inclusive. Productivity of entrepreneurs with disabilities in 3 elements of the value chain, namely procurement, product/service development and distribution, was observed to be significant. The Study showed that disability-related knowledge of entrepreneurs with disabilities could contribute to business performance according to the key success factors to enhance added value. Two elements of the value chain, namely sales/marketing and customer service, are not the decisive factors to define and clarify disability-inclusiveness. Conclusion: Settings in Southeast Asia are diverse and at varying stages of economic and social development; hence the environment which promotes the disability-inclusive business concept may be inconsistent. Micro and smallscale rural businesses were tackled as a first step to evaluate comparative efforts of each case of disability-inclusive business from the viewpoint of entrepreneurs with disabilities. Therefore, in highlighting the differences, it is recommended that further research should seek to apply weighting factors depending on the individual size, contents and scale of major business areas.